Karakterisasi Beberapa Sifat Kuantitatif Plasma Nutfah Gandum (Triticum aestivum. L) - Sri Gajatri Budiarti (Buletin Plasma Nutfah, 2005)
The aim of the experiment were to rejuvenate and characterize of wheat germplasm. Eighty nine genotypes planted at Kuningan Field Research Instalation, West Java from June to October 2002. Plot size for each genotypes 3 x 1 m2 with spacing 25 x 10 cm. Seeds were planted with 2 seed per hole and thinned out to one plant. Several agronomic characters were observed: date of flowering, date of maturing, plant height, number of productive tiller per hill, seed weight per hill and yield per plot. The results showed that: date of flowering (mean 60.9 days with range 48-77 days), date of maturity (mean 102.7 days with range 87-119 days), plant height (mean 72.4 cm, range 53.5-88.7 cm), number of productive tiller per hill (mean 9.71, range 4.9-24.0), seed weight per hill (mean 11.96 g, range 5.3-34.5 g) and seed yield per plot (200.0- 2624.5 g). Seventeen genotypes have date of flowering <54.3 days, some of them were H40, H80, V219, and V132. There were 25 genotypes have date of harvesting ranged 87-98 days, some of them were H40 (87 days), H85 (91 days), H90 (91 days). There were 16 genotypes have plant height <65.2 cm, some of them were C3 (53.5 cm), C7 (58.4 cm), C14 (59.1 cm). Whereas the highest was C10 (88.7 cm). Nine genotypes have number of productive tiller per hill >17.5, some of them were C8 (23.6), C27 (22.7) and the greatest number was C28 (24.0). Sixty six genotypes have number of productive tiller per hill, ranged 4.9-11.2, some of them were: C34 (4.9), C24 (5.2), H85 (5.6). Seed weight per hill showed that 60 genotypes have seed weight <12.6 g, for example: H71 (5.3 g), H40 (6.6 g), C132 (5,4 g), C34 (6,7 g), whereas the heaviest was C28 (34.5 g). Sixteen three two genotypes that have yield per plot >2000 g were V192 (2016.0 g), and V167 (2624.5 g). AbstrakTujuan penelitian adalah merejuvenasi dan mengkarakterisasi plasma nutfah gandum, terutama morfologi dan agronomi. Penelitian dilaksanakan pada Juni hingga Oktober 2002 di Inlitpa Kuningan, Jawa Barat. Sejumlah 89 genotipe gandum ditanam pada petak berukuran 3 x 1 m2, dengan jarak tanam 25 x 10 cm, secara tugal, dua biji per lubang, dan diperjarang menjadi satu tanaman. Pemupukan dilakukan pada 1 MST secara alur di samping barisan tanaman. Pupuk dasar terdiri dari 100 kg urea, 200 kg SP36, dan 50 kg KCl/ha. Sejumlah 100 kg urea/ha diberikan lagi pada umur 5 MST dan 9 MST. Karakterisasi dilakukan terhadap umur berbunga, umur masak, tinggi tanaman, jumlah anakan produktif per rumpun, bobot biji per rumpun, dan hasil biji per petak. Umur berbunga ratarata 60,9 hari dengan rentang 48-77 hari, umur masak 102,7 hari dengan rentang 87-119 hari, tinggi tanaman 72,4 cm dengan rentang 53,5-88,7 cm, jumlah anakan produktif per rumpun 9,71 dengan rentang 4,9-24, bobot biji per rumpun 11,96 g dengan rentang 5,3-34,5 g, dan hasil biji per petak berkisar antara 200-2624,5 g. Genotipe yang mempunyai umur berbunga <54,3 hari di antaranya adalah H40, H80, V219, dan V132. Genotipe yang mempunyai umur masak 87-98 hari di antaranya adalah H40, H85, dan H90. Genotipe dengan tinggi tanaman <65,2 cm di antaranya adalah C3, C7, dan C14. Genotipe dengan jumlah anakan produktif per rumpun >17,5 di antaranya adalah C28, C8, C27. Genotipe yang mempunyai jumlah anakan produktif 4,9-11,2 di antaranya adalah C34, C24, dan H85. Genotipe yang mempunyai bobot biji <12,6 g, di antaranya adalah H71, H40, V132, C34, dan yang terberat adalah genotipe C28. Dua genotipe yang mempunyai hasil biji per petak >2000 g adalah V192 dan V167.